Experimental oral infection in chickens (Gallus gallus domesticus) with Neospora caninum (NC-SP1) oocysts - Oliveira, Solange de (2017)
Neospora caninum is a tissue-cyst forming parasite that belongs to the phylum Apicomplexa. Dogs and other canids are the definitive hosts of N. caninum and they are responsible to excrete oocysts, the environmentally resistant stage of the parasite. Viable parasites have been isolated from a variety of species, especially herbivorous, confirming their role as intermediate hosts. The importance of birds in the life cycle of N. caninum is not clear. Several experiments, using tachyzoites as inoculum, were conducted in domestic and wild birds and the results were not conclusive. In nature, the possible mode of transmission in chickens is the ingestion of oocysts. This work aimed to evaluate the infection by N. caninum in chickens orally inoculated with oocysts obtained from a new isolate of N. caninum. For that, approximately 400 g of brain from a naturally infected adult cattle, showing anti-N. caninum antibodies by means of the immunfluorescent antibody test - IFAT (titre = 200), were fed to a 2-month-old dog. Neospora-like oocysts were observed on day 7 post-inoculation (p.i.). The DNA obtained from oocysts was molecularly characterized using the ITS-1 marker and the final sequence was 99% identical to homologous sequences of N. caninum. Gerbils (Meriones unguiculatus) were orally inoculated with different doses of oocysts (10, 100 and 1000 oocysts), and all of them remained clinically normal and developed N. caninum antibodies 14 days p.i. (titre ≥ 50 by IFAT). Brain homogenate from an infected gerbil was seeded into a monolayer of Vero cells and tachyzoites were visualized at 24 days p.i.. Microsatellite genotyping using DNA from the tachyzoites revealed a unique genetic profile for this new reference isolate, named NC-SP1. Thirty White Leghorn chickens (Gallus gallus domesticus) were orally inoculated with viable N. caninum oocysts from the NC-SP1 isolate (200 oocysts per bird) via the crop at 21 days of age. Groups of three birds were euthanized at intervals of 7 days during 9 weeks; one group was challenged with the same oocysts dose at 37 days p.i. and observed for 11 weeks. Blood samples were collected weekly, and sera were tested by IFAT. Chicken tissues were analyzed using PCR, quantitative PCR and immunohistochemistry (IHC). Two mongrel dogs, approximately 45 days of age were fed with tissues from chickens euthanized at 138 and 159 days p.i.. The chickens did not seroconvert (titre < 5), and neither DNA (PCR and qPCR) nor antigen (IHC) of N. caninum was detected in inoculated chicken tissues. In addition, no oocyst excretion by the dogs was observed. In these experimental conditions, the chickens were resistant to N. caninum infection.